The Impact of Green HRM Policies and Employee Green Behavior on Organizational Sustainability in the East Java Manufacturing Industry - Soelistianto, Farida Arinie; Usup, Usup; Kurniawan, Nur Hasan (West Science Interdisciplinary Studies, 2025)
This study explores the impact of Green Human Resource Management (GHRM) policies and green employee behavior on organizational sustainability within the manufacturing industry in East Java. A quantitative research design was employed, using a sample of 160 respondents and a Likert scale (1-5) to collect data. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was used to analyze the relationships between the variables. The results show that GHRM policies significantly positively influence green employee behavior and organizational sustainability. Furthermore, green employee behavior was found to mediate the relationship between GHRM policies and organizational sustainability. These findings suggest that the implementation of green HRM practices plays a crucial role in encouraging environmentally responsible behaviors, ultimately contributing to the overall sustainability of the organization. This research offers valuable insights for manufacturing organizations seeking to enhance their sustainability practices through effective human resource management.